Dynamic force identification based on composite trigonometric wavelet shape function. (July 2020) - He, Wen-Yu; Wang, Yang; Ren, Wei-Xin
Highlights: A dynamic force identification approach based on composite trigonometric wavelet. The challenge task of determining the time unit length in advance can be avoided. The trigonometric wavelet performances better than the polynomial functions. The identification accuracy can be enhanced progressively according to actual needs. Abstract: The shape function-based methods are promising in dynamic force identification. However, the selection of shape function is still an issue as it determines the identification accuracy and efficiency to a large extent. This paper proposes a dynamic force identification approach by using the composite trigonometric wavelet as shape function which takes advantage of its 'wave' property in dynamic force expression. The whole domain of the dynamic force time history is segmented into different time units following the thought of finite element discretization and the local force is approximated by linear shape functions. Subsequently the force-response equation is established by assembling the calculated responses induced by shape function forces and the corresponding measured responses of all time units. Then trigonometric wavelet shape function is added to enhance the approximation capability of shape function and improve the identification accuracy progressively. Examples are employed to illustrate the effectiveness and superiority of the proposed method.